2015
DOI: 10.1016/j.neuropsychologia.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion recognition impairments are associated with brain volume abnormalities in individuals with HIV

Abstract: Impaired facial emotion recognition abilities in HIV+ patients are well documented, but little is known about the neural etiology of these difficulties. We examined the relation of facial emotion recognition abilities to regional brain volumes in 44 HIV-positive (HIV+) and 44 HIV-negative control (HC) adults. Volumes of structures implicated in HIV− associated neuropathology and emotion recognition were measured on MRI using an automated segmentation tool. Relative to HC, HIV+ patients demonstrated emotion rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 83 publications
3
32
0
Order By: Relevance
“…HIV+ adults have been reported to exhibit reduced facial emotion recognition abilities relative to HC adults (Baldonero et al 2013; Clark et al 2010a; Clark et al 2015; Heilman et al 2013; Lane et al 2012). Hence, we assessed the effects of facial emotion recognition abilities on amygdala responses in our sample.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…HIV+ adults have been reported to exhibit reduced facial emotion recognition abilities relative to HC adults (Baldonero et al 2013; Clark et al 2010a; Clark et al 2015; Heilman et al 2013; Lane et al 2012). Hence, we assessed the effects of facial emotion recognition abilities on amygdala responses in our sample.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we assessed the effects of facial emotion recognition abilities on amygdala responses in our sample. Facial emotion recognition abilities were assessed utilizing methods employed in prior studies (Circelli et al 2013; Clark et al 2010a; Clark et al 2008, 2010b; Clark et al 2015). Briefly, participants were presented with 70 Ekman and Friesen photographs (Ekman & Friesen, 1976) on a 15″ laptop computer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Nevertheless, peripheral viral suppression has not always prevented progressive cognitive and motor impairment, and the origin of these behavioral effects during treatment is still debated, with several ART-era studies demonstrating structural associations with cognitive deficits during treatment. [4][5][6] Early brain structural studies in HIV-infected participants found decreases in brain parenchyma, 7 white matter, 8 and basal ganglia 7,9 volume. During the ART era, observations of cortical, 10 subcortical, gray matter, 9 and white matter 10 atrophy have continued, with decreases in cortical gray matter and brain parenchymal volume observed even in the first year of HIV infection.…”
mentioning
confidence: 99%